Exploring the Potential of Synthetic Cannabinoids: Modulation of Biological Activity of Normal and Cancerous Human Colon Epithelial Cells - Roman Paduch; Katarzyna Szwaczko; Kamil Dziuba; Adrian Wiater (Cells)
Colorectal cancer (CRC) is a global problem. Oncology currently practices conventional methods of treating this carcinoma, including surgery, chemotherapy, and radiotherapy. Unfortunately, their efficacy is low; hence, the exploration of new therapies is critical. Recently, many efforts have focused on developing safe and effective anticancer compounds. Some of them include cannabinoids. In the present study, we obtained cannabinoids, such as cannabidiol (CBD), abnormal cannabigerol (abn-CBG), cannabichromene (CBC), and cannabicitran (CBT), by chemical synthesis and performed the biological evaluation of their activity on colon cancer cells. In this study, we analyzed the effects of selected cannabinoids on the lifespan and metabolic activity of normal colonic epithelial cells and cancer colon cells. This study demonstrated that cannabinoids can induce apoptosis in cancer cells by modulating mitochondrial dehydrogenase activity and cellular membrane integrity. The tested cannabinoids also influenced cell cycle progression. We also investigated the antioxidant activity of cannabinoids and established a relationship between the type of cannabinoid and nitric oxide (NO) production in normal and cancerous colon cells. To conclude, it seems that, due to their interesting properties, the cannabinoids studied may constitute an interesting target for further research aimed at their use in alternative or combined therapies for human colon cancer.